2014
DOI: 10.1021/es405524b
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Epigenetic Mechanisms Underlying Enhanced in Vitro Adipocyte Differentiation by the Brominated Flame Retardant BDE-47

Abstract: Recent studies suggest that exposure to endocrine-disrupting compounds (EDCs) may play a role in the development of obesity. EDCs such as the flame retardant 2,2′,4,4′-tetrabrominated diphenyl ether (BDE-47) have been shown to enhance adipocyte differentiation in the murine 3T3-L1 model. The mechanisms by which EDCs direct preadipocytes to form adipocytes are poorly understood. Here, we examined transcriptional and epigenetic mechanisms underlying the induction of in vitro adipocyte differentiation by BDE-47. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 42 publications
(103 reference statements)
3
76
1
Order By: Relevance
“…Moreover, di(2-ethylhexyl) phthalate (DEHP) or its metabolite mono-(2-ethylhexyl) phthalate (MEHP) increased adipocyte differentiation in 3T3-L1 cells, (142) (115), murine mesenchymal stem cells (44), and in vivo (142) (62). Few human studies have addressed effects of BFRs on obesity and metabolic syndrome; however, adipocyte differentiation was increased by the BFRs PDBE (397) and BDE-47 (185). These findings are supported by a recent study which reported increased body weight of obese mice treated with hexabromocyclododecane (HBCD) (431).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…Moreover, di(2-ethylhexyl) phthalate (DEHP) or its metabolite mono-(2-ethylhexyl) phthalate (MEHP) increased adipocyte differentiation in 3T3-L1 cells, (142) (115), murine mesenchymal stem cells (44), and in vivo (142) (62). Few human studies have addressed effects of BFRs on obesity and metabolic syndrome; however, adipocyte differentiation was increased by the BFRs PDBE (397) and BDE-47 (185). These findings are supported by a recent study which reported increased body weight of obese mice treated with hexabromocyclododecane (HBCD) (431).…”
Section: Effects Of Pops On At Functionmentioning
confidence: 99%
“…In 3T3-L1 cells, BDE-47 increased in Ppar␥2 expression levels, which was associated with a decrease in DNA methylation of the Ppar␥2 promoter. Also increased levels of several adipogenic genes were found after BDE-47 exposure, including Lep, but no changes in DNA methylation of the leptin promoter were found (36). Though perinatal exposure to BDE-47 resulted in increased body weight in rodents (37), to our knowledge, epigenetic analysis linking developmental exposure to the obesogenic effects of BDE-47 in vivo has not been performed.…”
Section: Obesogenic Edc Exposure and Epigenetic Effectsmentioning
confidence: 93%
“…BDE-47 binds and activates human PPAR␥ in vitro (36). In 3T3-L1 cells, BDE-47 increased in Ppar␥2 expression levels, which was associated with a decrease in DNA methylation of the Ppar␥2 promoter.…”
Section: Obesogenic Edc Exposure and Epigenetic Effectsmentioning
confidence: 94%
“…Lipid accumulation and cell number were analysed according to a previously described method [3]. Zebrafish were exposed during early development (0-5 days) to MEHP and the internal concentration of secondary metabolites was defined to confirm metabolism of phthalates by the embryo.…”
Section: Referencesmentioning
confidence: 99%
“…Regulatory guidance for non-clinical safety studies to support the initiation of clinical trials involving pregnant subjects is available from FDA and WHO [3]. FDA guidance states that for products indicated specifically for immunization of pregnant women, data from non-clinical developmental toxicity studies should be available prior to initiation of clinical trials enrolling pregnant subjects.…”
mentioning
confidence: 99%